International agreements involve in the insurance market in the frame of the European Private International Law - Aguilar Grieder, Hilda (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This study analyses the law applicable treatment to the contracts involve in the insurance market. The fragmentation of the conflict of law solutions relating to the contracts involve in the insurance market led to effects in the internal market. It is necessary to find a solution to that problems.
Keywords: European Private International Law; international agreements; international contracts involve in the insurance market; fragmentation of the conflict of law solutions; effects to the internal market